2011
DOI: 10.20873/jbb.uft.cemaf.v2n3.silva
|View full text |Cite
|
Sign up to set email alerts
|

Wild strains of fermenting yeast isolated of sugar cane juice from an alcohol distillery from Mato Grosso, Brazil

Abstract: A produção de etanol é importante para a economia nacional constituindo-se em solução renovável para complementar derivados de petróleo. O processo industrial utiliza leveduras disponíveis comercialmente, a maioria das quais isoladas em usinas do estado de S. Paulo. Não se têm conhecimento sobre a disponibilidade de leveduras selecionadas para as condições climáticas da região Centro Oeste. O artigo apresenta os resultados do isolamento e caracterização morfológica de levedurasselvagens fermentativas obtidas d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 6 publications
0
6
0
3
Order By: Relevance
“…Embora os dois trabalhos reportem a caracterização cultural de leveduras, é possível relacionar as diferenças a origem das cepas dos dois trabalhos. SILVA et al (2011) isolaram e caracterizaram leveduras de caldo de cana de uma destilaria de álcool de Mato Grosso do Sul, no Centro-oeste brasileiro, mesmo substrato da pesquisa em questão. Os autores reportaram 16 diferentes morfotipos de colônias, superior a desse estudo, onde nove grupos coloniais foram detectados (TABELA 1).…”
Section: Resultsunclassified
See 2 more Smart Citations
“…Embora os dois trabalhos reportem a caracterização cultural de leveduras, é possível relacionar as diferenças a origem das cepas dos dois trabalhos. SILVA et al (2011) isolaram e caracterizaram leveduras de caldo de cana de uma destilaria de álcool de Mato Grosso do Sul, no Centro-oeste brasileiro, mesmo substrato da pesquisa em questão. Os autores reportaram 16 diferentes morfotipos de colônias, superior a desse estudo, onde nove grupos coloniais foram detectados (TABELA 1).…”
Section: Resultsunclassified
“…Embora, as características macroscópicas sozinhas, não sejam suficientes para identificação de leveduras, as mesmas se constituem uma importante ferramenta no processo clássico de identificação (SILVA et al, 2011) e são sugestivas da diversidade desse grupo microbiano. Nesta pesquisa, o agrupamento das cepas de leveduras em nove grupos diferentes indica a diversidade cultural das mesmas no caldo de cana.…”
Section: Gruposunclassified
See 1 more Smart Citation
“…All the yeast isolates showed zones of clearance during the screening for citric acid production but with varying diameters. It was concluded that pineapple wastes, pineapple wastes and sugar cane juice is potentially a suitable source to select fermentative yeasts (Silva et al, 2011). It was observed that even isolates that was identified as the same species gave different diameters of clearance which could be attributed to being different strains of the same species.…”
Section: Discussionmentioning
confidence: 99%
“…The annual production of citric acid is estimated to be about 1.4 to 1.5 million tons per year and its demand is estimated to be growing at a rate of about 3.5 to 4.0% annually (Soccol et al, 2006;Lazar et al, 2011;Show et al, 2015). Of the total amount of citric acid produced annually, about 70% is utilized by the food industry; about 12% is utilized by pharmaceutical industries as flavouring, anticoagulant and preservative while the remaining 18% is utilized by other industries such as cosmetics, detergent, textile, oil recovery and paper (Soccol and Vandenberghe, 2003;Silva et al, 2011). Citric acid is also used in the detergent industry as a phosphate substitute, because of less eutrophic effect, and in the cement industry to slow down the process of hardening (Max et al, 2010).…”
mentioning
confidence: 99%